Chelation of hippocampal zinc enhances long-term potentiation and synaptic tagging/capture in CA1 pyramidal neurons of aged rats: implications to aging and memory - Shetty, M.S (Blackwell Publishing Ltd, 2020)
10.1111/acel.12537